Visualizing Toll-like Receptor-dependent Phagosomal Dynamics in Murine Dendritic Cells Using Live Cell Microscopy - Mantegazza, Adriana R. (Methods Mol Biol, 2015)
Dendritic cells are professional phagocytes that are highly specialized to process and present antigens from internalized particles to prime naïve T cells. To achieve their functions, the phagocytic machinery and membrane dynamics of these cells have been adapted to optimize presentation of antigens from phagocytosed particles that bear ligands of pattern recognition receptors, such as toll-like receptors (TLRs), and that are thus perceived of as “dangerous”. We have recently shown that phagosomes that are engaged in TLR signaling in dendritic cells emit numerous long tubules that facilitate content exchange with other signaling phagosomes and favor presentation of particle-derived antigens. This chapter describes the methods used to study the formation of these tubules, which we refer to as “phagotubules”, by live cell imaging of mouse dendritic cells after the phagocytosis of fluorescent latex beads. We also describe methods to assess the effect of TLR signaling on this process.